Levels of Salivary IFN-gamma, TNF-Alfa, and TNF Receptor-2 As Prognostic Markers in (Erosive) Oral Lichen Planus - Noha A. Ghallab; Naglaa El-Wakeel; Olfat G. Shaker (Mediators of Inflammation)
To explore the feasibility of detecting salivary levels of IFN-γ, TNF-α, and sTNFR-2 from erosive oral lichen planus (ELP) patients for clinical application, 20 ELP patients were enrolled in the study as were 20 age-sex-matched controls. From all subjects, saliva level of the tested biomarkers was determined by ELISA. Salivary profiles were assessed in ELP patients by ELISA after being treated with prednisone. A significantly higher level of IFN-γ (P≤.01), TNF-α (P≤.0001), and sTNFR-2 (P≤.01) was detected in ELP patients before treatment than in controls. Following treatment, the salivary levels of IFN-γ (P≤.01), TNF-α (P≤.05), and sTNFR-2 (P≤.01) decreased significantly when compared to their pretreatment levels. This study demonstrated that salivary IFN-γ, TNF-α, and sTNFR-2 can be detectable in ELP patients and decreased significantly after treatment with prednisone, which may reveal the possibility of using these disease-related biomarkers in diagnosis and monitoring.